A homozygous nonsense CEP250 mutation combined with a heterozygous nonsense C2orf71 mutation is associated with atypical Usher syndrome. Issue 7 (29th April 2014) - Khateb, Samer; Zelinger, Lina; Mizrahi-Meissonnier, Liliana; Ayuso, Carmen; Koenekoop, Robert K; Laxer, Uri; Gross, Menachem; Banin, Eyal; Sharon, Dror
Abstract : Background: Usher syndrome (USH) is a heterogeneous group of inherited retinitis pigmentosa (RP) and sensorineural hearing loss (SNHL) caused by mutations in at least 12 genes. Our aim is to identify additional USH-related genes. Methods: Clinical examination included visual acuity test, funduscopy and electroretinography. Genetic analysis included homozygosity mapping and whole exome sequencing (WES). Results: A combination of homozygosity mapping and WES in a large consanguineous family of Iranian Jewish origin revealed nonsense mutations in two ciliary genes: c.3289C>T (p.Q1097*) in C2orf71 and c.3463C>T (p.R1155*) in centrosome-associated protein CEP250 (C-Nap1). The latter has not been associated with any inherited disease and the c.3463C>T mutation was absent in control chromosomes. Patients who were double homozygotes had SNHL accompanied by early-onset and severe RP, while patients who were homozygous for the CEP250 mutation and carried a single mutant C2orf71 allele had SNHL with mild retinal degeneration. No ciliary structural abnormalities in the respiratory system were evident by electron microscopy analysis. CEP250 expression analysis of the mutant allele revealed the generation of a truncated protein lacking the NEK2-phosphorylation region. Conclusions: A homozygous nonsense CEP250 mutation, in combination with a heterozygous C2orf71 nonsense mutation, causes an atypical form of USH, characterised by early-onset SNHL and a relatively mild RP. The severe retinal involvement in the double homozygotes indicates an additive effect caused by nonsense mutations in genes encoding ciliary proteins.